UJI ANTIINFLAMASI EKSTRAK ETANOL BIJI PETAI (PARKIA SPECIOSA HASSK.) TERHADAP MENCIT PUTIH (MUS MUSCULUS) JANTAN YANG DIINDUKSI KARAGENIN - Latipah, Latipah; Rizka Mulya Miranti,; Tuty Mulyani, (Journal of Innovation Research and Knowledge, 2024)
Petai seeds contain phenolic compounds, flavonoids, terpenoids, and steroids which are thought to have a role in anti-inflammatory effect. In this study, the anti-inflammatory effect of petai seed extract was tested using the paw edema method induced by 1% carrageenin. The test was carried out by dividing 5 groups, namely negative control, positive control and ethanol extract of petai seeds with doses of 100,200 and 300 mg/kgBW. In this study, there were 4 test parameters, namely the percent edema, AUC (Area Under Curve), the percent inhibition of inflammation, and the percent relative potential of anti-inflammatory power. The test data were analyzed by analysis of variance (ANOVA) then followed by the Post Hoc test using the LSD (Least Square Differences) method with a 95% confidence level to see the differences between treatments. Based on the results of these tests, the results stated that the administration of ethanol extract of petai seeds had anti-inflammatory power with the best dose of 300 mg/kgBB.